2019
DOI: 10.1088/1757-899x/567/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hierarchical clustering methods (case study: data on poverty influence in North Sulawesi)

Abstract: Grouping of Large data has been carried out in various fields. One method for grouping is cluster analysis where this method consists of hierarchy and non-hierarchy method. The aim of this study was to compare the use of cluster analysis on aspects of the causes of poverty data. The method used is agglomerative hierarchical clustering, that is, the average linkage, centroid methods and ward methods. The results obtained are compared with the RMSSTD value and the smallest value is the ward method with a value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…It was demonstrated that cluster genesis through combined HC's linkage and dissimilarity algorithms & NNC is more reliable than individual optical assessment of NNC, where varying a map size in SOM will alter the association of inputs' weights to neurons, providing a new structure of the clusters. Moreover, HC-classification of predictors Na (9), SO 4 (11); pH (2), Turbidity (3),…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was demonstrated that cluster genesis through combined HC's linkage and dissimilarity algorithms & NNC is more reliable than individual optical assessment of NNC, where varying a map size in SOM will alter the association of inputs' weights to neurons, providing a new structure of the clusters. Moreover, HC-classification of predictors Na (9), SO 4 (11); pH (2), Turbidity (3),…”
Section: Discussionmentioning
confidence: 99%
“…6, is presented in Table 4, second row and third row display the number of links at different levels and their inconsistency coefficients, respectively. Here, inconsistency coefficient '0' corresponds to the links joining the pairs NO 3 (12) & F (15), Mg (6) & Cl (8), Ca (5) & As (16) and Na ( 9) & SO 4 (11) in Fig. 6, as there is no link joining the variables below them.…”
Section: Hierarchical Clustering (Hc)mentioning
confidence: 99%
See 2 more Smart Citations
“…Grouping is based on similarities or distance (dissimilarity). The clusters are aggregated according to a decreasing degree of similarity (or increasing degree of dissimilarity) into one single tree-like cluster, called a dendrogram [ 33 ].…”
Section: Methodsmentioning
confidence: 99%